Pengembangan Panduan Digital Berbasis Klarifikasi Nilai Empatik Pencegahan Mikroagresi Bias Gender Guru Di Sekolah Dasar - Rafli, Muhammad; Latif, Suciani; Umar, Nur Fadhilah (Indonesian Journal of Educational Counseling, 2023)
This study aims to develop guidelines for empathetic communication methods for teachers and students in preventing gender bias microaggressions based on flip book media. This research method uses Hannafin and Peck's model development research. This development research applies steps starting from the stages of needs analysis, design, product development, material and media expert testing, revision, and user testing. The subjects of this study were 20 elementary school teachers in Makassar City. The research data collection technique uses a needs analysis questionnaire, expert validation, and user trials in the form of a Google form using a Likert scale. Data analysis techniques using descriptive and reflective data analysis. The results showed that the teacher's level of need for digital guidance was 90% and was categorized as feasible through validation by media and material experts at 90% and through the user test process with a high level of media feasibility. This shows that the teach-smart digital guide is appropriate in reducing and preventing microaggressions caused by the teacher's gender bias behavior in the learning process.